Multifunctional Textiles with Flame Retardant and Antibacterial Properties: A Review - Liping Jin; Chenpeng Ji; Shun Chen; Zhicong Song; Juntong Zhou; Kun Qian; Wenwen Guo (Molecules, 2023)
It is well known that bacterial infections and fire-hazards are potentially injurious in daily life. With the increased security awareness of life and properties as well as the improvement of living standards, there has been an increasing demand for multifunctional textiles with flame retardant and antibacterial properties, especially in the fields of home furnishing and medical protection. So far, various treatment methods, including the spray method, the dip-coating method, and the pad-dry-cure method, have been used to apply functional finishing agents onto fabrics to achieve the functionalization in the past exploration stage. Moreover, in addition to the traditional finishing technology, a number of novel technologies have emerged, such as layer-by-layer (LBL) deposition, the sol-gel process, and chemical grafting modification. In addition, some natural biomasses, including chitin, chitosan (CS), and several synthetic functional compounds that possess both flame-retardant and bacteriostatic properties, have also received extensive attention. Hence, this review focuses on introducing some commonly used finishing technologies and flame retardant/antibacterial agents. At the same time, the advantages and disadvantages of different methods and materials were summarized, which will contribute to future research and promote the development and progress of the industry.